Las Costumbres y Tradiciones en el Desarrollo de la Cultura Kichwa de los niños y niñas de quinto grado básico del Centro Educativo General Básica “Martha Bucarám de Roldós” de la comunidad Tranca San Luis, parroquia Cebadas, cantón Guamote, provincia Chimborazo período lectivo 2014-2015 - Guaminga Chuquimarca, Segundo Víctor (2016)
This research paper called the customs and traditions in the development of the Kichwa culture in children enrolled in fifth grade of basic education at "Martha Bucaram de Roldos" school which focused on the goal of making a diagnosis to children in order to identify the incidence of customs and traditions in the development of the Kichwa culture, the approach and formulation of the problem followed by justification based on their importance, relevance, beneficiaries, feasibility and impact. In the theoretical framework of scientific substantiation reference related to the philosophical, epistemological, pedagogical, psychological, and legal axiological issues. Regarding the theoretical foundation, it is based on concepts, relevant content of the independent variable, in this case, it corresponds to the customs and traditions, while the dependent variable is the development of the Kichwa culture. The population corresponds to 28 children in the fifth grade. Then the technique of observation to children based on the observation sheet as an instrument were data was processed through statistical tables and graphs that allowed the analysis and interpretation of results to identify problems and determine conclusions and recommendations. The obtained results focused on identifying language and strengthen the Kichwa culture, maintaining high self-esteem to boost their language and identify their customs and traditions in order to engage oral expression using their ancestral language in any social context.